2013
DOI: 10.1016/j.jcat.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Structure control of silica-supported mono and bimetallic Au–Pt catalysts via mercapto capping synthesis

Abstract: a b s t r a c tSiO 2 -supported monometallic and bimetallic platinum-gold catalysts are prepared by deposition of metal nanoparticles stabilized by mercaptopropyltriethoxysilane (MPTES) after different aging time of the solution containing metal ions and MPTES. The materials are tested in the hydrodesulfurization (HDS) reaction of thiophene and compared with corresponding catalysts prepared by the conventional deposition-precipitation (DP) method. The monometallic Pt and the bimetallic Au-Pt prepared by DP hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…If we compare the frequency of the linearly adsorbed CO for Pt and 1Au/1Pt catalysts, i.e. the Pt 0 -CO band, after the evacuation at 100 • C for 30 min (Table 3), we will see that below 300 • C the frequency of the Pt-CO band is higher for the 1Au/1Pt catalysts and close to the band at 2060 cm −1 previously attributed to CO adsorbed on the bimetallic Au-Pt nanoparticles [61]. Anyway, this could be also due to CO adsorption on bigger Pt NPs in the bimetallic 1Au/1Pt catalyst, the presence of such NPs was proved by the STEM study.…”
Section: [Auclsupporting
confidence: 70%
See 1 more Smart Citation
“…If we compare the frequency of the linearly adsorbed CO for Pt and 1Au/1Pt catalysts, i.e. the Pt 0 -CO band, after the evacuation at 100 • C for 30 min (Table 3), we will see that below 300 • C the frequency of the Pt-CO band is higher for the 1Au/1Pt catalysts and close to the band at 2060 cm −1 previously attributed to CO adsorbed on the bimetallic Au-Pt nanoparticles [61]. Anyway, this could be also due to CO adsorption on bigger Pt NPs in the bimetallic 1Au/1Pt catalyst, the presence of such NPs was proved by the STEM study.…”
Section: [Auclsupporting
confidence: 70%
“…Multilayer deposition of Au and Pt could lead to partial coverage of Au NPs with platinum as it was described above. Moreover, La Parola et al [61] reported the decrease in the surface Au/Pt ratio determined by XPS in AuPt/SiO 2 catalysts while increasing the thickness of the platinum shell on the surface of the gold core during the aging of the solution of Au and Pt precursors with mercaptopropyltriethoxysilane. Another reason was the presence of big Au/Pt agglomerates, which were observed by STEM.…”
Section: [Auclmentioning
confidence: 99%
“…Thus, one can expect different interaction of silver and platinum species with NH 2 groups in APTMS and SH in MPTMS. It should be emphasized that in the case of chloroplatinic acid used as a Pt source, protons can modify aminopropyl chain in APTMS towards the formation of NH 3 + interacting with PtCl 6 2− [7,14,16,37]. SH groups in MPTMS exhibit weakly acidic character and therefore can directly interact with PtCl 6 2− .…”
Section: Influence Of the Preparation Methods On The State Of Mono Anmentioning
confidence: 99%
“…Pt and Ag are amongst the most popular transition metals used for catalytic oxidation [1][2][3]. Recently, a significant development has been made in the preparation of supported bimetallic AuPt nanoparticles [4][5][6][7][8][9][10]. Silver-platinum nanoparticles are not so well known.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that capping ligands are employed in colloidal synthesis to stabilize NP size and/or morphology, and they may have impact on catalyst properties, namely catalytic activity and selectivity. The documented behaviors vary from inhibitory effects, such as a surface poisoning observed for size-controlled Co NPs co-stabilized with phosphine oxide ligands during CO 2 /H 2 reaction; [8] and promotional effects, such as a ligand-induced creation of active surface ensembles in the case of thiol-stabilized monometallic Pt and bimetallic Au-Pt NPs for hydrodesulfurization reactions [9]. Partial activity losses were also reported for Suzuki coupling [10], ethylene hydrogenation [11][12][13], and the hydrogenative isomerization of methylcyclopentane [14] when using polymer (e.g.…”
Section: Introductionmentioning
confidence: 99%